Sixteenth Century North America : The Land and the People As Seen by the Europeans. - Sauer, Carl Ortwin (University of California Press, 2022)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1971.
Description based upon print version of record.
Keywords: America -- Discovery and exploration.; North America -- Discovery and exploration.; Explorers -- North America -- History.; Explorers -- America -- History.; America -- History -- To 1810.; America -- Colonization.; Amérique -- Découverte et exploration.; Amérique du Nord -- Découverte et exploration.; Explorateurs -- Amérique du Nord -- Histoire.; Explorateurs -- Amérique -- Histoire.; Amérique -- Histoire -- Jusqu'à 1810.; Amérique -- Colonisation.; Colonization.; Discoveries in geography.; Explorers.; America.; North America.; To 1810; History.